The Marquesan collection at the British Museum, London : genesis, growth and statis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Massey University, Manawatu, Palmerston North, New Zealand - McKinney, Natasha R (Massey University, 2012)
This thesis examines the formation of the collection from the Marquesas Islands, French Polynesia, at the British Museum in London. Specifically, it investigates the historical and museological factors which have influenced acquisition over time, and questions why the collection was not expanded in the second half of the twentieth century. Marquesan culture is outlined, in order to contextualise the circumstances in which objects were first collected, and to gain insight into both indigenous and outsider priorities in these exchanges. The dramatic impact of contact, and colonisation by the French, facilitates an understanding of the major changes in artistic production over the nineteenth and twentieth centuries, which led to the cessation of certain art forms, the persistence of others, and the creation of completely new categories. This establishes, therefore, what was available for collection. Archival research served to trace objects to the moment of collection, and to reveal the main characters and transactions which led to their acquisition by the Museum. It emerges that individual collectors and curators played a central role in the growth and composition of the collection – attitudes of the latter being strongly influenced by contemporary anthropological theory. The main factors which contributed to the stasis of the collection are the relatively limited availability of Marquesan objects in comparison to earlier periods, combined with the persistence of negative attitudes towards objects which demonstrated significant external influence. The manner in which the collection has been presented to the public via exhibitions is also studied, revealing the multiple redefinitions of the objects and their role within the Museum and scholarly discourse over the course of the collection’s existence. A clear and persistent bias towards the earliest collected material becomes apparent throughout. The thesis argues that the composition of the collection has served to maintain this bias, and to restrict the development of new exhibition initiatives, which may have created the impetus for renewed collecting. A reassessment is suggested, in light of changing museum practice and the contemporary relevance of the collection for Marquesans.
Keywords: British Museum; Ethnological collections; Marquesans; Marquesas Islands; Art; Material culture